Ethan Kleinberg, Haunting History: For a Deconstructive Approach to the Past - Pelekanidis, Theodoros (Historein, 2019)
Review of Ethan Kleinberg. Haunting History: For a Deconstructive Approach to the Past. Stanford: Stanford University Press, 2017. 208 pp.